Reconstruction of Strengthening the Right to Sustainable Groundwater (Assessing Model Policy in Bandar Lampung City) - Pane, Erina (Hasanuddin Law Review, 2016)
Implementation of sustainable development related to the management of groundwater resources in the area can be realized with the establishment of a policy which is inseparable from the values prevailing in the society. The formation of ground water resources management policies is not only technically partial, but must also be comprehensive-holistic. Groundwater management activities include the conservation and utilization of groundwater organized to realize the sustainability and continuity of availability of groundwater and its sustainable benefit. Water resources policy in the form of government intervention should be able to improve the efficient use of water resources in an optimal and sustainable and should provide reinforcement right to water for the community. Weight of policy should be placed in a fair way, where the public interest, private interest and the government’s interest is positioned in a balanced condition, but with the requirement that the parties are jointly responsible for creating actions in environmental improvements.